A study of hydrogen leak and explosion in different regions of a hydrogen refueling station. (30th April 2023) - Liu, Kun; He, Canxing; Yu, Yongzhe; Guo, Chaoya; Lin, Simin; Jiang, Jieyu
Abstract: The consequences of hydrogen leaks and explosions are predicted for the sake of the safety in hydrogen refueling stations. In this paper, the effect of wind speed on hydrogen leak and diffusion is analyzed in different regions of a hydrogen refueling station, and the influence of delayed ignition time on hydrogen explosion after an accidental hydrogen leak is further studied by numerical simulation. Results show that the effect of wind speed on the probability of hydrogen fires is distinctive in different regions of hydrogen refueling station. The size of combustible clouds in the trailer front region and the outer region increases in the low wind speed case, and the front of combustible clouds is formed in a spherical shape in the outer region, which can greatly increase the probability of hydrogen explosion. However, the high wind speed may cause an increase of the risk of accidents in the near ground region. Moreover, a non-linear correlation is shown between the rate of combustible cloud dissipation and wind speed after the hydrogen stops leaking. In addition, it is found that an increase in delayed ignition time may lead to an increase in explosion intensity, which is related with the larger high temperature area and stronger explosion overpressure. Two flame fronts and the reverse propagation of the explosion overpressure can be observed, when the delayed ignition time is larger. Highlights: The risk of hydrogen fires in different regions is analyzed. The fire risk in the near ground region increases with increasing wind speed. Two flame fronts are captured in explosion process. A longer delayed ignition time may lead to an increase in the explosion intensity.